Autonomous learning practices of extrovert and introvert EFL learners - Savitri, Wiwiet Eva (JEES (Journal of English Educators Society), 2021)
Learning autonomy has been widely seen as a key predictor of a language learning success. There have been many studies on learning autonomy, however, most studies do not investigate how students conduct their autonomous learning. The number of those which investigate how learning autonomy is implemented across personality type is even fewer. To address it, this article will elaborate how extrovert and introvert students managed their autonomous learning. The objectives of this article are to reveal how extrovert and introvert learners perceive autonomous learning and to know the types of activities which were done by the extrovert and introvert learners and their reasons for doing the activities. Interviews and observation were applied to collect data. The findings indicate that autonomous learning was carried out differently by both personality types. Introvert students devoted more time and focused on their solitude learning and they are more organized in doing it. On the other hand, extrovert learners chose to do the autonomous learning in groups. For them, learning in a community gave more benefits. One of the benefits was preventing them from making fossilized errors. This article also reveals that the students from both personality types used digital technology in learning independently. Yet, extrovert and introvert students used different kinds of technology and way in using it. HIGHLIGHTS: Autonomous learning does not merely mean learning alone because it refers to self-trigger to learn, both individually and in groups. Extrovert and introvert learners have different perception and apply different strategies in implementing autonomous learning. Extrovert and introvert students implement autonomous learning, shedding light on their perceptions, activities, and the role of digital technology in the process.